« Marchands de nature » : 20 ans de communication institutionnelle dans la métropole lyonnaise de 1989 à 2009 - Inès Méliani; Paul Arnould (VertigO)
In the current debate “how the major cities attach importance to the notion of the nature?”, the metropolis of Lyon constitutes an exemplary case. In the competitive climate in which Lyon is compared to the other big European metropolises, promotional speeches carrying by communications groups exploit the nature issue. The following reflection is based on a lexicometric analysis of the Lyons institutional press dated from 1989 to 2009. A diachronic approach question the use of the nature issue under the successive mandates of Michel Noir, Raymond Barre and Gerard Collomb. A use of techniques in quantitative and qualitative data treatment puts in context and gives sense to the content of these articles. The analysis of all the newspapers covering the study period is about 441 articles. The results show the ambivalence of the nature issue in urban environment. In the beginning of 1990’s, the metropolis of Lyons introduces the methods of action and the resources of his environmental policy. Twenty years later, the improvement of the soil gains ground to the detriment of natural area. Between concrete, long-lasting action and territorial marketing, we postulate the nature issue as a more and more exploited notion. The mobilization of nature objects combines philosophic references, social preoccupations, ecological goals and commercial aspects. The nature is not necessarily the same from each other.